2010
DOI: 10.1103/physrevc.81.064608
|View full text |Cite
|
Sign up to set email alerts
|

Analytical parametrization of fusion barriers using proximity potentials

Abstract: Using the three versions of proximity potentials, namely proximity 1977, proximity 1988, and proximity 2000, we present a pocket formula for fusion barrier heights and positions. This was achieved by analyzing as many as 400 reactions with mass between 15 and 296. Our parametrized formula can reproduced the exact barrier heights and positions within an accuracy of $\pm1%$. A comparison with the experimental data is also in good agreement.Comment: 12 pages, 5 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(83 citation statements)
references
References 70 publications
4
74
0
Order By: Relevance
“…As noted above, a careful analysis of [11,12] has shown that the potentials due to AW 95, Bass 80, Denisov DP and Proximity 2010 yield close agreement with experimental data. All these potentials were parameterized in terms of the proximity concept [12,[14][15][16].…”
Section: Description Of Modelssupporting
confidence: 59%
See 1 more Smart Citation
“…As noted above, a careful analysis of [11,12] has shown that the potentials due to AW 95, Bass 80, Denisov DP and Proximity 2010 yield close agreement with experimental data. All these potentials were parameterized in terms of the proximity concept [12,[14][15][16].…”
Section: Description Of Modelssupporting
confidence: 59%
“…[11], Dutt and Puri carried out a massive hunt for the best nucleon-nucleon potential by carefully analyzing about a dozen proximity based potentials, robust for a large number of empirical fusion barriers. There, the potentials due to AW 95, Bass 80 and Denisov DP were found to reproduce barrier heights and positions far better than others in the class [11]. In addition to many extensions of the original proximity potential, Dutt and Bansal [12] also proposed a new form of proximity potential (labelled as Prox.…”
Section: Introductionmentioning
confidence: 99%
“…Dutt and R. K. Puri in Ref. [28] modified PROX 2000 by including the nuclear radii given by Royer and Rousseau [29]. This modified version is named as PROX 2000DP.…”
Section: Proximity 2000 Dp (Prox 2000dp)mentioning
confidence: 99%
“…Among such attempts, proximity model [22][23][24][25] is well known for its simplicity. In this model, the nuclear part of the interaction potential is given as the product of the geometrical factor and the universal function.…”
Section: Introductionmentioning
confidence: 99%
“…Fusion in heavy-ion reactions has been one of the most extensively studied topics in nuclear physics over the last decades [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Various attempts have been made to explain this phenomenon by using a variety of theoretical models based on different assumptions.…”
Section: Introductionmentioning
confidence: 99%